Measurement and Empirical Study on High-Quality Development Index of Sports Industry - A Case Study of Shanghai, China - Kang, Lu (Quality in Sport, 2025)
The high-quality development of China's sports industry represents a pivotal national strategy requiring systematic evaluation mechanisms. This study establishes a multidimensional indicator system through systematic literature review and Delphi expert consultation, encompassing four foundational dimensions (industrial foundation, quality, efficiency, and motive power), 11 secondary and 35 tertiary indicators. We employ a novel "dscatter degree evaluation method" to develop a dynamic evaluation model enabling temporal comparisons and spatial benchmarking. Empirical validation through longitudinal measurement (2014-2020) of Shanghai's sports industry reveals a 150.91% growth trajectory in its high-quality development index, while spatial analysis identifies distinct regional polarization patterns. Our findings demonstrate the system's capacity to transform empirical assessments into quantifiable metrics, providing an empirical framework for data-driven policy formulation in sports-developed urban centres. The methodology offers replicable tools for monitoring industrial transformation efficiency and optimizing resource allocation strategies in emerging sports economies.